Basel II and Operational Risk: Implications for risk measurement and management in the financial sector - Ariane Chapelle; Yves Crama; Georges Hubner; Jean-Philippe Peters (National Bank of Belgium, 2004)
This paper proposes a methodology to analyze the implications of the Advanced Measurement Approach (AMA) for the assessment of operational risk put forward by the Basel II Accord. The methodology relies on an integrated procedure for the construction of the distribution of aggregate losses, using internal and external loss data. It is illustrated on a 2x2 matrix of two selected business lines and two event types, drawn from a database of 3000 losses obtained from a large European banking institution. For each cell, the method calibrates three truncated distributions functions for the body of internal data, the tail of internal data, and external data. When the dependence structure between aggregate losses and the non-linear adjustment of external data are explicitly taken into account, the regulatory capital computed with the AMA method proves to be substantially lower than with less sophisticated approaches allowed by the Basel II Accord, although the effect is not uniform for all business lines and event types. In a second phase, our models are used to estimate the effects of operational risk management actions on bank profitability, through a measure of RAROC adapted to operational risk. The results suggest that substantial savings can be achieved through active management techniques, although the estimated effect of a reduction of the number, frequency or severity of operational losses crucially depends on the calibration of the aggregate loss distributions.
Keywords: C24; G18; G21; 330; operational risk management; basel II; advanced measurement approach; copulae; external data; EVT; RAROC; cost-benefit analysis.; Basler Akkord; Kreditrisiko; EU-Staaten; Basler Akkord